A multi‐jurisdictional outbreak of Salmonella Typhimurium infections linked to backyard poultry—Australia, 2020. (3rd July 2022) - Laidlow, Troy A.; Stafford, Russell; Jennison, Amy V.; Bell, Robert; Graham, Rikki; Graham, Trudy; Musgrave, Natasha; Myerson, Mark; Kung, Nina; Crook, Allison; Wang, Qinning; Richards, Alun; et al.
Abstract: Zoonotic salmonellosis can occur either through direct contact with an infected animal or through indirect contact, such as exposure to an infected animal's contaminated environment. Between May and August 2020, a multi‐jurisdictional outbreak of Salmonella Typhimurium (STm) infection due to zoonotic transmission was investigated in Australia. In total, 38 outbreak cases of STm with a median age of 5 years were reported. Epidemiological investigation showed contact with live poultry to be a common risk factor with most cases recently purchasing one‐week old chicks from produce/pet stores. Traceback investigation of cases identified 25 product/pet stores of which 18 were linked to a single poultry breeder farm. On farm environmental sampling identified the same STm genotype as identified in cases. Whole genome sequencing of both environmental and human outbreak isolates found them to be highly related by phylogenetic analysis. This investigation describes the first documented widespread zoonotic salmonellosis outbreak in Australia attributed to backyard poultry exposure and identified potential risk factors and prevention and control measures for future outbreaks. Prevention of future outbreaks will require an integrated One Health approach involving the poultry industry, produce/pet store owners, animal healthcare providers, public health and veterinary health agencies and the public.